Optimization of drug therapy in elderly individuals admitted to a geriatric unit - Piau A (Dove Medical Press, 2017)
Antoine Piau,1 Yoann Huet,1 Adeline Gallini,2,3 Laurine Andre,1–3 Bruno Vellas,1–3 Fati Nourhashemi1–3 1Gérontopôle, Centre Hospitalier Universitaire Toulouse, Toulouse, France; 2UMR1027, INSERM-University of Toulouse, Toulouse, France; 3Department of Epidemiology and Public Health, Centre Hospitalier Universitaire Toulouse, Toulouse, France Background: A substantial share of adverse drug events involves inappropriate prescribing (IP). Specialized geriatric units are supposed to pay particular attention to prescribing appropriateness and to promoting a higher prescribing quality.Objective: The objective of this study was to evaluate the reality of such assessment and optimization in real life (usual care) in a population of elderly individuals admitted to a geriatric unit.Method: This is an observational study including all older patients admitted to an acute geriatric unit over a 6-month period. As part of usual care, the geriatrician is supposed to detect potentially inappropriate medication and potential prescribing omission using validated tools. The primary outcome was the prevalence rate of therapeutic modifications motivated by treatment optimization (stop, switch, or introduction). Multivariate logistic regression analyses were performed to identify the factors associated with therapeutic discontinuation.Results: A total of 216 patients were included. The mean age was 85.7 years. Included patients had an average of 7.2±3.3 drugs at admission and 5.8±2.7 at discharge. IP was highly prevalent in our study where about 63% of the patients had experienced at least one modification because of overuse. The most commonly discontinued medications were drugs used to treat gastroesophageal reflux disease and peptic ulcer disease and serotonin reuptake inhibitor antidepressants. The most commonly introduced medications were analgesics and warfarin. By using multivariate analysis, we found that patient age and number of drugs on admission were significantly associated with medication discontinuation during hospital stay.Conclusion: In this real-life study of all patients admitted to a Geriatric Post Emergency Unit, 83% of the patients had a treatment modification during hospital stay. The most original result of our study is the clear reduction in polypharmacy during hospitalization. Keywords: elderly, inappropriate prescriptions, geriatric unit, overuse, misuse, underuse